The Urgency of HR Quality in Improving the Quality of Islamic Education Institutions - Yuni Masrifatin (EDUCATIO: Journal of Education)
Human Resources (HR) Education is the potential that is an asset and material / non-financial in the school organization, which can be realized into real potential (real) physically and non-physically in realizing the existence of the organization / school. Human Resources consists of two dimensions, namely the qualitative dimension and the quantitative dimension. The qualitative dimension includes various potentials contained in every human being, including thoughts (ideas), knowledge, attitudes, and skills that influence the capacity of human ability to carry out productive work. Meanwhile, the quantitative dimension consists of the achievements of students, the quality of educational institutions and the number of teachers and education personnel in the amount of learning time.  If spending to improve the quality of human resources (Human Resources) is increased, the productivity value of human resources (Human Resources) will produce a positive rate of return. Human resources are very important for the progress of all educational institutions. Moreover, Islamic educational institutions are institutions that are considered perfect by the community as institutions that make students have competence in the fields of science and religion. Strengthening all aspects of HR (Human Resources) becomes absolutely necessary in Islamic religious education institutions, competent HR (Human Resources) will bring changes in the institution to the expected goodness and progress.